Orthorhombic LiMnO2 nanorods as cathode materials for lithium-ion batteries: Synthesis and electrochemical properties. Issue 7 (15th May 2016) - Zhao, Hongyuan; Liu, Shanshan; Liu, Xingquan; Tan, Ming; Wang, Zhenwei; Cai, Yu; Komarneni, Sridhar
Abstract: A simple solid-state process was developed to prepare the orthorhombic LiMnO2 nanorods by using Mn2 O3 nanorods as a template, the latter was prepared via a thermal decomposition process. The obtained product showed good rod-shaped morphology and could be indexed to the orthorhombic LiMnO2 with a space group of Pmnm. Electrochemical tests showed that the LiMnO2 nanorods exhibited a discharge capacity of 183.2 mA h g −1 with high coulombic efficiency at 0.1 C between 2.0 and 4.3 V. After 35 cycles, the discharge capacity still reached up to 175.6 mA h g −1, which is a high capacity retention. Furthermore, the LiMnO2 nanorods presented excellent rate capability and small charge transfer resistance. Such high performance might be ascribed to the one-dimensional nanostructures with good crystallinity, which could effectively facilitate the charge and electron transport and enhance the electrode-filled ratio.